2018
DOI: 10.1186/s13059-018-1593-z
|View full text |Cite
|
Sign up to set email alerts
|

Understanding tumor ecosystems by single-cell sequencing: promises and limitations

Abstract: Cellular heterogeneity within and across tumors has been a major obstacle in understanding and treating cancer, and the complex heterogeneity is masked if bulk tumor tissues are used for analysis. The advent of rapidly developing single-cell sequencing technologies, which include methods related to single-cell genome, epigenome, transcriptome, and multi-omics sequencing, have been applied to cancer research and led to exciting new findings in the fields of cancer evolution, metastasis, resistance to therapy, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
115
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(122 citation statements)
references
References 210 publications
(221 reference statements)
0
115
0
Order By: Relevance
“…The utility of this strategy has been widely shown in many tumor types and the quantification of CTCs can be used as a prognostic factor [45]. Whereas many authors claim that CTCs recapitulate intratumor diversity perfectly, others have reported that they resemble metastasis more than primary tumors [46].…”
Section: Circulating Tumor Cellsmentioning
confidence: 99%
“…The utility of this strategy has been widely shown in many tumor types and the quantification of CTCs can be used as a prognostic factor [45]. Whereas many authors claim that CTCs recapitulate intratumor diversity perfectly, others have reported that they resemble metastasis more than primary tumors [46].…”
Section: Circulating Tumor Cellsmentioning
confidence: 99%
“…Single‐cell transcriptome sequencing (scRNA‐seq) has opened new avenues for the understanding of the biological role of cell populations, their origins, and interactions (Ren et al , 2018). Single‐cell approaches – in contrast to bulk tissue sequencing – allow to determine which cell type is responsible for transcriptomic changes, which is of fundamental importance for the understanding of tumor biology.…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in cancer immunotherapies have provided paradigm shifts in treating patients with advanced malignancies. The development and therapeutic use of various immunotherapy regimens rely on the systems‐level understanding of cellular composition, interaction, and dynamics of the tumor ecosystem . Tumors are infiltrated with immune, stromal, and other cell types, leading to extraordinary intratumor heterogeneity, which plays a vital role in tumor progression and requires new methods such as single‐cell multiomics approaches and systems‐level analysis to tackle.…”
mentioning
confidence: 99%